Development of an in vitro model to estimate mass transfer from the anterior cavity - Liu, Tianyang; Ibeanu, Nkiruka; Brocchini, Steve; Khaw, Peng Tee; Bouremel, Yann; Awwad, Sahar (Frontiers in Drug Delivery, 2022)
Knowledge of drug mass transfer from the anterior chamber via the iris-lens barrier has important implications for the development of front of the eye medicines that can also deliver drugs to the vitreous cavity. Here, the design and evaluation of a novel in vitro model that estimates anterior clearance (CL) kinetics is described. To mimic some aspects of the human eye to aid with pharmaceutical modelling, the model incorporated a simulation of aqueous inflow from the ciliary inlet at the physiological flow rate, two CL elimination pathways [anterior hyaloid pathway and retina choroid sclera (RCS) pathway], human cavity dimensions and use of simulated vitreous fluid (SVF). An eye movement platform that incorporated 3 different eye movements (smooth pursuit, microsaccadic and saccadic) was tested against the control (no movement) to observe any difference in anterior kinetics profile and drug convection to the posterior cavity. Both timolol and brimonidine injected in the intracameral space were evaluated in the new in vitro prototype. An initial release study with one selected eye movement (smooth pursuit) with timolol (6.8 ± 0.4 µg, 30 μL) and brimonidine (15.3 ± 1.5 µg, 30 μL) showed half-life values of 105.3 and 97.8 min respectively in the anterior cavity (AC) space. Another study evaluated the effect of all eye movements against control with both drugs with higher doses of timolol (146.0 ± 39.1 μg, 25 μL) and brimonidine (134.5 ± 39.5 μg, 25 μL). The amounts of timolol in the back of the eye (RCS membrane and outflow) were 0.07 ± 0.05%, 1.36 ± 0.88%, 1.55 ± 1.03% and 0.98 ± 0.06% by 8 h with smooth pursuit, microsaccadic, saccadic and no movement respectively; whereas brimonidine amounts were 0.70 ± 0.21%, 0.94 ± 0.40%, 1.48 ± 1.02%, and 0.76 ± 0.33% respectively. A small amount of both drugs was seen in other compartments in the model (lens part, iris part, hyaloid membrane part and silicone cornea). These results indicate that this model can be used to determine transfer of small molecules via the iris-lens barrier to help optimise front of the eye formulations to treat tissues further back in the eye.